On photo‐electron angular distributions from clusters. Issue 4 (13th March 2013) - Wopperer, Philipp; Reinhard, Paul‐Gerhard; Suraud, Eric
<x xml:space="preserve">Abstract</x> The distributions of electrons emitted from a metal cluster after laser excitation are analyzed from a theoretical perspective. The focus is laid on the angular distributions of the emitted electrons taking, in particular, the anisotropy as measure for the basic shape. This observable is discussed at various levels of sophistication, from stationary perturbation theory to a fully dynamical simulation of the electron dynamics using time‐dependent density‐functional theory. The simple most approach, perturbation theory with outgoing plane waves, can be treated mostly analytically which provides useful, qualitative insights into the mechanisms determining the angular distributions. Comparing the model, an extreme sensitivity of the results to all details of the cluster has been found. This requires a theoretical description without compromises. Using a fully dynamical simulation with detailed ionic background yields generally smooth trends for the frequency dependence of the anisotropy, with emission preferably along the laser polarization plus some isotropic background. Weakly bound cluster ions make an exception for frequencies near emission threshold where a generic tendency to sidewards emission prevails.